2020
DOI: 10.33314/jnhrc.v18i3.1674
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Visual Inspection of Cervix with Acetic Acid and Liquid Based in Cervical Cancer Screening with Cervical Biopsy

Abstract: Background: Cervical cancer is the second most common cancer among women in developing countries. Cervical cancer generally develops slowly over a period of 10-15 years. Incidence and mortality related to cervical cancer both have declining in developed countries because of effective screening programs through Papanicolaou smear. Therefore, cervical cancer can be prevented through implementation of different methods of screening programs like visual inspection of cervix with application of acetic acid visual i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In 2020 Shrestha [12] conducted a study in which researchers performed colposcopy with aqueous AA and delayed histopathological verification in 144 women. Achieved sensitivity, specificity, PPV and NPV accounted for 81%, 65%, 61% and 83%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2020 Shrestha [12] conducted a study in which researchers performed colposcopy with aqueous AA and delayed histopathological verification in 144 women. Achieved sensitivity, specificity, PPV and NPV accounted for 81%, 65%, 61% and 83%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The study confirmed the superiority of liquid diagnostics over the colposcopic evaluation of the cervix. However, the survey concerned a small group of patients [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At multivariable analysis only alcohol consumption and HIV status remained significantly negatively associated with VIA positivity. The prevalence of a positive VIA based on what others have reported ranges from 10-43% [ 10 - 12 ]. Cervical VIA is recommended for low resource settings [ 13 ], it is cheap and its performance is comparable to the Papanicolaou test [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] The uses of vinegar are summarized in Table 1 . [ 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 ]…”
Section: Introductionmentioning
confidence: 99%